Вплив пірацетаму та прамірацетаму на агрегаційну активність тромбоцитів за умов алоксанового діабету у щурів - Мамчур, В. Й.; Жилюк, В. І.; Лівих, А. Е. (Clinical Endocrinology and Endocrine Surgery, 2009)
Research of influence of nootropic drugs piracetam and pramiracetam on platelets aggregative ability in conditions of rat alloxan diabetes was carried out. The analysis of received results has shown that modeling of alloxan diabetes in rats leads to platelets’ aggregative ability augmentation. Administration of investigated drugs in diabetic rats had different effects on platelets functional activity. Piracetam practically had no influence on induced platelet aggregation indicators, while pramiracetam administration led to expressed antiaggregative effect in diabetic rats. This fact is the prerequisite for the further studying of this question in clinical conditions. Administration of pramiracetam with the purpose of cognitive functions normalization of patients with diabetes can have additional benefits comparing with piracetam.